Le Liber Iudiciorum et ses différentes versions - Céline Martin (Mélanges de la Casa de Velázquez, 2011)
The fact that numerous leges antiquae in the Liber are anonymous can surely be ascribed to a damnatio memoriae passed on the Arian monarchs by the compilers. The first compilation of the Liber, in 654, was done in a context of opposition by Recceswinth to his father, recently deceased. However, the code was retroactive and authorised the annulment of acts dating back to Chindaswinth; this was tantamount to a rescissio actorum, which would also ensue from a damnatio memoriae. Besides its practical purpose, the Liber thus has an ideological dimension, defining as it does good kings and bad kings. Whether or not Recceswinth wished it to be the sole source of law produced by the courts, the Liber is in fact neither exhaustive nor entirely uniform, for many laws are clearly the products of case law. Failure to consider the lacunae in the Liber has led to the erroneous conclusion that Ervige repealed the military law of Wamba (LV IX, 2, 8), whereas in fact both their laws, as set out in the code, were valid at the same time.